2021
DOI: 10.1186/s12936-021-03858-0
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes for malaria management: the evolution from 1980 to 2020

Abstract: Malaria is one of the most prevalent parasitic diseases and the foremost cause of morbidity in the tropical regions of the world. Strategies for the efficient management of this parasitic infection include adequate treatment with anti-malarial therapeutics and vaccination. However, the emergence and spread of resistant strains of malaria parasites to the majority of presently used anti-malarial medications, on the other hand, complicates malaria treatment. Other shortcomings of anti-malarial drugs include poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 270 publications
(463 reference statements)
0
23
0
Order By: Relevance
“…We only picked up some typical examples from lots of liposomal natural products for the demo (Table 1). Artemisinin, isolated from Artemisia annua L., was discovered in 1972 to treat malaria by Youyou Tu who was awarded the Nobel Prize in physiology or medicine (Figure 2) (Isacchi et al, 2011a;Memvanga and Nkanga, 2021). It also showed activities in chemotherapeutic drug for tumors and lupus erythematosus (Mu and Wang, 2018).…”
Section: Liposomal Medicinal Natural Productsmentioning
confidence: 99%
“…We only picked up some typical examples from lots of liposomal natural products for the demo (Table 1). Artemisinin, isolated from Artemisia annua L., was discovered in 1972 to treat malaria by Youyou Tu who was awarded the Nobel Prize in physiology or medicine (Figure 2) (Isacchi et al, 2011a;Memvanga and Nkanga, 2021). It also showed activities in chemotherapeutic drug for tumors and lupus erythematosus (Mu and Wang, 2018).…”
Section: Liposomal Medicinal Natural Productsmentioning
confidence: 99%
“…Nanoformulations, i.e., nanoparticlulate systems are colloidal dispersions of very small size ranging from 1 to 1000 nm, with a high surface area in relation to their volume, and whose morphology and properties depend on their components and preparation methods [ 184 , 185 ]. They have several applications, including their use as drug carriers.…”
Section: Current Lipid- and Inorganic-based (Metal Or Metal Oxide) Na...mentioning
confidence: 99%
“…Malaria has been a major global health problem for humans throughout their history and is a leading cause of mortality across many tropical and subtropical countries ( Hemingway and Bates, 2003 ; Cowman et al, 2016 ; Monroe et al, 2022 ). Malaria control efforts have been undermined by the decline in the effectiveness of the primary malaria-figurehting tools, increasing resistance to treated-insecticide nets and anti-malarial drugs, and no effective vaccine ( Olotu et al, 2013 ; Haldar et al, 2018 ; Memvanga and Nkanga, 2021 ). Spotlights from the 2022 world malaria report by WHO showed that cases of malaria increased from 245 million in 2020 to 247 million in 2021, although malaria-related deaths slightly decreased from 625,000 to 619,000 ( World Health Organization, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The etiological agent of malaria, Plasmodium, mainly thrives in human and mosquito hosts. Of all Plasmodium parasites, five species are responsible for global malaria infections in humans: Plasmodium falciparum , Plasmodium vivax , Plasmodium malariae , Plasmodium ovale , and Plasmodium knowlesi ( Lalremruata et al, 2017 ; Memvanga and Nkanga, 2021 ; Sato, 2021 ).…”
Section: Introductionmentioning
confidence: 99%